O007 Pancreas and islet transplantation in the United Kingdom during the COVID-19 era. (22nd July 2022) - Counter, C; Owen, R; Sinha, S; Muthusamy, A; Drage, M; Callaghan, C; Elker, D; Harper, S; Sutherland, A; Van Dellen, D; Johnson, P; Manas, D; et al.
Abstract: Introduction: WHO declared a pandemic of COVID-19 in March 2020. This study analyses the impact of COVID-19 on beta-cell replacement therapy in the UK. Methods: Pancreas and islet donation and transplant activity in the period March 2020/2021 was compared with the same period the previous year. Results: 2, 180 patients had a functioning graft during March 2020/2021. 5.8%(n=126) tested positive for COVID-19 and two died (1%). In this period there was a 43% reduction in solid organ donors n=1, 615, compared with the previous year, n=2, 840. Of the 625 solid organ donors with a pancreas offered, 32% had the pancreas retrieved compared with 51% the previous period. 97 whole pancreas and islet transplants were performed in the UK down 54% from the prior period. Of the 84 pancreas transplant recipients; four tested positive for COVID-19 but none died, and two grafts failed within the first week from vascular thrombosis (neither were COVID-19 positive). Of the 13 SIK and islet alone transplant recipients, two tested positive for COVID-19 but neither died. Of these SIK transplants, one is known to have failed within a month and this is equivalent to that seen in the previous time period. To our knowledge, no patient receiving beta cell replacement therapy died of COVID during the first year of the pandemic despite immunosuppression. Conclusion: In the UK, pancreas, and islet transplantation have continued during the pandemic at a lower rate. Outcomes following transplantation within the COVID era are, so far, similar to those in the period prior. Take-home message: Outcomes following transplantation within the COVID era are, so far, similar to those in the period prior.